1992
DOI: 10.1111/j.1464-5491.1992.tb01710.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hypoglycaemic Agents on the Growth and Metabolism of Human Endothelial Cells

Abstract: Using human umbilical vein endothelial cells, and human microvascular endothelial cells from omental and subcutaneous fat obtained at laparotomy, we studied the effects of sulphonylureas and the biguanide metformin on endothelial cell proliferation, prostacyclin production, ecto-5'-nucleotidase activity, and von Willebrand factor release. Each drug produced a concentration-dependent proliferation of umbilical vein but not of microvascular endothelial cells. The stimulation of umbilical vein endothelial cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Different authors have investigated the effects of metformin on the proliferation of other cell types. This biguanide did not influence cell proliferation in cultured arterial smooth muscle cells, human dermal fibroblasts, umbilical artery-derived smooth muscle cells or 3T3 fibroblastic cells (Peuler et al, 1996;Petty and Pearson, 1992). In the present in vitro study, we present data that clearly shows a proliferative effect of metformin on osteoblast-like cells, in a concentration range similar to that used by other authors (Peuler et al, 1996;Petty and Pearson, 1992).…”
Section: Discussionsupporting
confidence: 76%
“…Different authors have investigated the effects of metformin on the proliferation of other cell types. This biguanide did not influence cell proliferation in cultured arterial smooth muscle cells, human dermal fibroblasts, umbilical artery-derived smooth muscle cells or 3T3 fibroblastic cells (Peuler et al, 1996;Petty and Pearson, 1992). In the present in vitro study, we present data that clearly shows a proliferative effect of metformin on osteoblast-like cells, in a concentration range similar to that used by other authors (Peuler et al, 1996;Petty and Pearson, 1992).…”
Section: Discussionsupporting
confidence: 76%
“…In agreement with these previous results, Zhen et al [61] demonstrated that metformin, at a similar concentration range, markedly increases proliferation of rat primary osteoblasts using the MTT assay. However, similarly to our results, metformin had no effect on cell proliferation in many other cell types including smooth muscle cells and endothelial cells [62,63]. This inconsistency regarding the proliferative effect of metformin and AICAR in different cell types as well as among various osteoblastic cell lines is still unclear and requires further investigation.…”
Section: Discussionsupporting
confidence: 63%
“…Many of the studies on metformin action centred on tissues directly involved in glucose homeostasis, such as skeletal muscle, adipose tissue and liver (Meyer et al, 1967;Wollen & Baily, 1988;Pedersen et al, 1989;Matthaei et al, 1991;Klip et al, 1992;Hundal et al, 1992;Sarabia et al, 1992;Fischer et al, 1995). In recent studies metformin was shown to inhibit the proliferation of human arterial smooth muscle cells and fibroblasts (Koschinsky et al, 1988); in endothelial cells from human umbilical vein, the effect of the drug was variable depending on its concentration (Petty & Pearson, 1992). However, the effect of metformin on the hexose transport system in vascular cells has not been investigated.…”
Section: Introductionmentioning
confidence: 99%